2011
DOI: 10.2106/jbjs.i.01623
|View full text |Cite
|
Sign up to set email alerts
|

The Osteoinductivity of Silicate-Substituted Calcium Phosphate

Abstract: The formation of bone within muscle during the twelve-week period showed both silicate-substituted calcium phosphate and stoichiometric calcium phosphate to be osteoinductive in an ovine model. Silicate substitution significantly increased the amount of bone that formed and the amount of bone attached to the implant surface. New bone formation occurred through an intramembranous process within the implant structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…47,49 Although it is recognized that both the rate of integration and the volume of regenerated bone may be dependent on features of the macroporosity, recent in vitro and in vivo studies have demonstrated biological sensitivity to the level of microporosity within the ceramic struts. [38][39][40][41][55][56][57][58][59] As can be seen in Fig. 8.4 , this so-called strut porosity or microporosity is of the order of only 1-20 μ m in size.…”
Section: Scaffold Permeability: Recreating Osteons and Canaliculaementioning
confidence: 97%
See 1 more Smart Citation
“…47,49 Although it is recognized that both the rate of integration and the volume of regenerated bone may be dependent on features of the macroporosity, recent in vitro and in vivo studies have demonstrated biological sensitivity to the level of microporosity within the ceramic struts. [38][39][40][41][55][56][57][58][59] As can be seen in Fig. 8.4 , this so-called strut porosity or microporosity is of the order of only 1-20 μ m in size.…”
Section: Scaffold Permeability: Recreating Osteons and Canaliculaementioning
confidence: 97%
“…More recently, the role of the strut microstructure and pore geometry has been considered with respect to the infl uence of these parameters on entrapment and recruitment of growth factors and matrix proteins 35 and the phenomenon of osteoinductivity, which will be discussed in more detail in sections 8.5 and 8.6. [36][37][38][39][40][41] © Woodhead Publishing Limited, 2013…”
Section: 4mentioning
confidence: 99%
“…Although these materials are known to be osteoconductive in nature by serving as scaffold for bone growth, they are also suggested to be osteoinductive; these materials by themselves actively stimulate differentiation of pre-osteoblastic cells to osteoblasts and formation of new bone 97,98 . Interestingly, all of these materials are highly enriched with Ca 2+ 99 , and their capacity to induce bone formation seems to differ depending on the amount of Ca 2+ .…”
Section: Molecular Perspectives: Common Properties Of Pulp-cappimentioning
confidence: 99%
“…However, the effect of silicon in substituted calcium phosphate materials was claimed to be overstated because a lack of experimental evidence linking the improved biological performance to silicon release [166]. For example, Coathup et al have reported osteoinductive silicatesubstituted calcium phosphate, but the stoichiometric counterpart in the study also triggered bone formation [167]. Additionally, the role of resorption and surface geometry, which might be provoked by silicon substitution, in the enhancement was not evaluated.…”
Section: The Effect Of Ion Substitution On the Physicochemical Propermentioning
confidence: 99%
“…In this thesis, canine, ovine and rabbits were employed but rodent and primates models are also often used in osteoinduction research [104,167,215,242,285,335]. These models showed significantly different osteoinductive potential [243,251,285].…”
Section: The Role Of Animal Modelsmentioning
confidence: 99%